Product packaging: research trends and opportunities - Zotos, Yorgos; Triantos, Al. (My University, 2014)
Product packaging has stimulated the interest of many researchers during the last decades. The aim of this study is to present the evolution of packaging studies and reveal the recent research trends. Toward this end, the authors used content analysis as a research method in order to categorise and analyse data from academic articles of the past fifty years. The findings of the study showed that there is an increasing trend toward packaging research which reached its peak during the last decade. An analysis by research theme identified the popular topics in packaging literature and the areas which remain unexplored. This study contributes to theory by demonstrating gaps in literature and offering opportunities for further research.
Keywords: Product packaging; Package elements; Content analysis; Research trends; Research opportunities